An 'unceasing war' on land development on the urban fringe of Beijing: A case study of gated informal housing communities. (February 2017) - Zhao, Pengjun
Abstract: The existing literature about informal development in China's cities is dominated by studies of conventional informal housing in urban villages, while a new type of informal housing, gated informal housing communities, has rarely been studied. The paper aims to contribute to the existing literature by discussing why and how these gated informal housing communities were developed, looking at the case of Beijing. The results of the analysis show that institutional discrimination against rural areas with respect to land use rights, revenue redistribution, policymaking procedures and the hukou -related social welfare system the major drivers of development of informal communities. In particular, informal development is influenced by the ways land value is captured by, compensated for and allocated to the state government rather than rural villagers in the process of its transfer from rural to urban land. For future policy, more institutional innovation or reform is imperative in order to adequately deal with the emergence of gated informal housing communities. Institutionally inclusive land and housing policies, rather than intense top-down control, are needed in China. Highlights: A new type of informal housing, gated informal housing communities, appeared. The gated informal housing communities reveals the growing tension between the state and local government. The institutional discriminations are major factors influencing the gated informal housing communities. The gated informal communities enhanced urban low-income earners' living situation.